CASE STUDY: NURSING CARE OF BRAIN-DEAD ORGAN DONORS - Nahathaiphokin, Janthana; Jerayingmongkol, Peranan; Kooariyakul, Ananya; Trakooljae, Ratchaneekorn; Areerob, Thitiporn; Mekdaeng, Kanyarat; Narissirikull, Chalalai (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2024)
The current trend of organ donation has significantly increased. Therefore, nursing care for patients with brain death is crucial. This academic article aims to present nursing care for organ donors with brain death based on real-life case studies in hospitals. The objective is to help nurses understand and be able to visualize the nursing care and treatment of organ donors, along with the healthcare team. This includes addressing the mental well-being of the donor's family. Nursing care for organ donors with brain death comprises three stages: 1) Pre-diagnosis stage: Nurses have to focus on identifying potential organ donors and negotiating organ donation with the patient's family, 2) Diagnosis stage: Nurses prepare the patient and assist physicians in accurately diagnosing brain death at every process, and 3) Post-diagnosis stage: Nurses provide comprehensive care to preserve the humanity of the donors and their families, helping them cope with the loss after organ donation.